Compliance to Diagnostic Reference Levels for radiation exposure in common radiological procedures in Dutch hospitals: A nation-wide survey carried out by medical imaging students. Issue 3 (August 2017) - Bijwaard, H.; de Vries, G.; Scheurleer, J.; Roding, T.; Erenstein, H.; Ravensbergen, W.; Haarmans-Jonkman, S.; van Welie, F.
Abstract: Introduction: In the Netherlands, hospitals have difficulty in implementing the formal procedure of comparing radiation dose values to Diagnostic Reference Levels (DRLs). Methods: To support the hospitals, train radiography students, and carry out a nationwide dose survey, diagnostic radiography students performed 125 DRL comparisons for nine different procedures in 29 radiology departments. Students were instructed at three Dutch Universities of Applied Sciences with a radiography programme and supervised by medical physicists from the participating hospitals. Results: After a pilot study in the western part of the country in eight hospitals, this study was enlarged to involve 21 hospitals from all over the Netherlands. The 86 obtained dose comparisons fall below the DRLs in 97% of all cases. This very high compliance may have been enhanced by the voluntary participation of hospitals that are confident about their performance. Conclusion: The results indicate that the current DRLs that were not based on a national survey, may need to be updated, sometimes to half their current value. For chest and pelvis examinations the DRLs could be lowered from 12 and 300 μGy·m 2 to the 75-percentile values found in this study of 5, 9 and 188 μGy·m 2, respectively. Highlights: Many hospitals in the Netherlands find the DRLs difficult to implement in practice. Radiography students were trained to assist hospitals in comparing doses to DRLs. DRLs have been checked by radiography students in 21 hospitals in the Netherlands. The results indicate that some DRLs could be lowered to half their current value.